2023
DOI: 10.3389/fspor.2023.1143376
|View full text |Cite
|
Sign up to set email alerts
|

Arthrogenic muscle inhibition after anterior cruciate ligament injury: Injured and uninjured limb recovery over time

Abstract: IntroductionIt is well documented that marked weakness of the quadriceps is present after knee joint injury. This joint trauma induces a presynaptic reflex inhibition of musculature surrounding the joint, termed arthrogenic muscle inhibition (AMI). The extent to which anterior cruciate ligament (ACL) injury affects thigh musculature motor unit activity, which may affect restoration of thigh muscle strength after injury, is undetermined.MethodsA randomized protocol of knee flexion and extension isometric contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Different explanations for the disagreement in the results emerge from the comparison of the experimental design used in our study with those of others [15,20,47,50,51]. First, the ACL of the participants enrolled in the present investigation was reconstructed using the combined semitendinosus-gracilis tendon (hamstring), whereas in the studies cited above, the harvest of a bone-patellar tendon bone (BPTB) was involved.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Different explanations for the disagreement in the results emerge from the comparison of the experimental design used in our study with those of others [15,20,47,50,51]. First, the ACL of the participants enrolled in the present investigation was reconstructed using the combined semitendinosus-gracilis tendon (hamstring), whereas in the studies cited above, the harvest of a bone-patellar tendon bone (BPTB) was involved.…”
Section: Discussionmentioning
confidence: 87%
“…However, in the literature, the higher hamstring activation in the ‘operated knee’ than in the ‘healthy knee’ was accompanied by quadriceps inhibition in the injured knee or on both sides during the maximal isometric contraction during the leg extension [ 15 , 20 , 47 , 50 , 51 ]. On the contrary, our study showed a higher VL (related to the peak of MVIC) and hamstring coactivation ratio (determined between VL-BF, RF-BF, and VM-BF in the initial portion of the force–time relationship, with RFD calculated with a window of 0.200 ms relative to the onset of MVICs) in the injured side than that in the uninjured side.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding the causes related to the deficiencies in quadriceps strength may result in early and successful management [9]. Recent Milad Zarrin, et al studies suggest that after undergoing ACLR, neural changes in electrocortical brain activity, the excitability of spinal reflex, and corticospinal pathways as well as in the central activation may contribute to the inadequate improvement of quadriceps strength and function [10][11][12]. These neural deficits have been associated with muscle weakness in the quadriceps, disordered movement patterns, and impairments in the voluntary activation of both the reconstructed and non-reconstructed limbs [10,13,14].…”
Section: Introductionmentioning
confidence: 99%